The Design and Implementation of Internet-Based Wireless Lan (WLAN) at Rawa Makmur Permai Urban Village Office - Pepi Pebrianti; Indra Kanedi; Yode Arliando (Penerbit Jurnal Indonesia, 2021)
This study aims to build an internet-based Wireless LAN (WLAN) at the Rawa Makmur Permai Urban Village Office, implement bandwidth and firewall management as a security system on the WLAN network, and observe the use of internet-based WLAN networks at the Rawa Makmur Permai Urban Village Office.This study uses the Development Life Cyle (NDLC) method which is a method that can be used in the network development process that allows network monitoring to determine network statistics and performance. The results of the performance analysis will later be taken into consideration in the design of network designs, both physical network designs or logical networks. The results of this study indicate that a WLAN network using a MikroTik router and implementing bandwidth management, firewalls and captive portals can optimize network usage, because by implementing bandwidth management it can distribute bandwidth evenly to clients according to their network access needs, the firewall itself can be used as a site access filtering system which in this study the author can apply to block the youtube.com site and make it a captive portal access.